Checklist of the birds of Colombia: A synthesis of the state of knowledge since hilty and brown (2017)
The taxonomy and knowledge of the distribution of Colombian avifauna has undergone great changes since the publication of “A Guide to the Birds of Colombia” by Hilty & Brown (1986) to the extent that we are unaware of how many and which species inhabit the Colombian territory. Here, we present a checklist of the birds of Colombia updated to August 2017 with a review of 340 references dealing with the distribution of Colombian birds. In sum, we report 1909 species for continental and insular Colombia, 216 of which have been added mainly since 1986. Although there are new data on distribution from 66% of the Colombian avifauna, most publications (87%) and new records (53%) are concentrated to the west of the Eastern cordillera (trans-Andean region). Based on the data we identify those regions of the country with knowledge gaps, which deserve more interest from researchers. Moreover, we encourage the ornithological community to publish their unpublished data and to improve the evidence supporting future new records for the country.